Creating a learning organization, creating a controlling organization: A case study of total quality management in an industrial setting - Sharon L. Howell; Judith A. Preston; Fred M. Schied; Vicki K. Carter (Adult Education Research Conference, 1996)
This study investigated the impact of a TQM program on hourly workers in an industrial setting. The paper argued that the basic skills program and the TQM process were implemented in the guise of education and training, but were driven by a corporate policy to reduce labor costs. The paper examined the way in which adult education was complicit in defining and controlling workplace knowledge. Data were collected through interviews with management personnel, education and training providers, and hourly workers.Hwang, Li-Shyung, North Carolina State University